Mindlessly Polite: A Conceptual Replication of the Emotional Seesaw Effect on Compliance and Information Processing - Kaczmarek, Magdalena C.; Steffens, Melanie C. (Frontiers in Psychology, 2017)
Recent studies demonstrated that the sequential induction of contrasting negative and positive emotions can be used as a social influence technique. The original field experiments found that whenever a sudden change in the emotional dynamic occurs – from negative to positive or vice versa – an increase in compliant behavior and an impairment in cognitive functioning can be observed. The goal of the present experiments was a conceptual replication and extension of the results in a more controlled and counterbalanced fashion. To this aim a novel emotion induction technique was created using an outcome related expectancy violation to induce and change emotions. In a first experiment the influence of contrasting emotions (vs. only one emotion) on compliance, message processing and information recall was assessed among 80 undergraduate students. We were able to show that a positive, then negative experience, and vice versa, led to losses in processing efficacy, not only leaving individuals momentarily vulnerable to social influence attempts, but also impairing information recall. We replicated this pattern of findings in a second experiment (N=41). The implications of this innovative induction technique and its findings for theory and future research on the emerging field on contrasting emotions as social-influence techniques are discussed.